2011
DOI: 10.1371/journal.pone.0016169
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intestinal Bacteria in Gliadin-Induced Changes in Intestinal Mucosa: Study in Germ-Free Rats

Abstract: Background and AimsCeliac disease (CD) is a chronic inflammatory disorder of the small intestine that is induced by dietary wheat gluten proteins (gliadins) in genetically predisposed individuals. The overgrowth of potentially pathogenic bacteria and infections has been suggested to contribute to CD pathogenesis. We aimed to study the effects of gliadin and various intestinal bacterial strains on mucosal barrier integrity, gliadin translocation, and cytokine production.Methodology/Principal FindingsChanges in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 54 publications
1
84
1
4
Order By: Relevance
“…Western blotting was performed as previously described. 37 The membranes were blocked with 2% (w/v) dry milk in 0.05% PBS-Tween-20 for 1 h at room temperature and incubated overnight at 4 uC with antibodies against occludin (1 : 1000) ZO-1 (1 : 1000) (Thermo Fisher Scientific, Waltham, MA, USA) and b-actin (1 : 5000) (Abcam, Cambridge, UK). After incubation with the respective primary antibodies, secondary staining was conducted using horseradish peroxidase-conjugated species-specific antibodies (1 : 1000) (Thermo Fisher Scientific, Waltham, MA, USA) for 1 h at room temperature.…”
Section: Western Blot Analysis Of Zo-1 and Occludinmentioning
confidence: 99%
“…Western blotting was performed as previously described. 37 The membranes were blocked with 2% (w/v) dry milk in 0.05% PBS-Tween-20 for 1 h at room temperature and incubated overnight at 4 uC with antibodies against occludin (1 : 1000) ZO-1 (1 : 1000) (Thermo Fisher Scientific, Waltham, MA, USA) and b-actin (1 : 5000) (Abcam, Cambridge, UK). After incubation with the respective primary antibodies, secondary staining was conducted using horseradish peroxidase-conjugated species-specific antibodies (1 : 1000) (Thermo Fisher Scientific, Waltham, MA, USA) for 1 h at room temperature.…”
Section: Western Blot Analysis Of Zo-1 and Occludinmentioning
confidence: 99%
“…Regarding the deregulation of goblet cells in CD, Cinova et al [139] observed that gliadin fragments and/or IFN-γ were able to reduce the number of PAS-positive goblet cells and increase mucin secretion in rat intestinal loops; interestingly, these changes were more pronounced in the presence of potentially pathogenic enterobacteria, while the decrease in PAS-positive goblet cells by gliadin was reversed by probiotics (B. bifidum IATA-ES2).…”
Section: Isc Modulation In CDmentioning
confidence: 99%
“…In celiac disease, rodent studies suggest that gut microbiota influences mucosal integrity and plays a role in the early pathogenesis of CD (Cinova et al, 2011). In human celiac disease, intestinal flora may be a key component switching oral tolerance to immune response against gliadin (Ray et al, 2012).…”
Section: Claudins and The Gut Microbiotamentioning
confidence: 99%